Graphene heat-conducting film and preparation method thereof

The graphitization of polyimide thin films is induced and catalyzed by graphene-supported nickel, which solves the problems of large energy consumption and unstable crystal structure of high-temperature graphitization method, and achieves the production of graphene thermally conductive films with lower energy consumption and better structure.

CN119430938AActive Publication Date: 2025-02-14SHENZHEN QIANHAI GRAPHENE IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411621213.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

In the existing polymer thin film graphitization method, the temperature is high and the energy consumption is high, the graphitized crystal structure is unstable, and there are problems of amorphous defects.

Method used

The graphitization of polyimide film is induced and catalyzed by graphene-supported nickel, which reduces the graphitization temperature, improves the graphitized crystalline structure, and reduces amorphous defects.

Benefits of technology

It greatly reduces production energy consumption, improves graphitized crystalline structure, reduces amorphous defects, and realizes the production of graphene thermally conductive films with lower energy consumption and better structure.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of electronic devices, in particular to a graphene heat conduction film and a preparation method thereof. Aiming at the problems of high temperature, high energy consumption, unstable graphitized crystalline structure and amorphous defects in the existing polymer film graphitization method, the invention provides the preparation method of the graphene heat-conducting film, nickel-loaded graphene powder is obtained by reacting water-soluble nickel salt with graphene, a viscous polyamide acid solution is generated in the reaction, and the graphene heat-conducting film is prepared. A polyimide composite film is obtained after imidization, and then the graphene heat conduction film is obtained after graphitization. According to the method, graphitization of the polyimide film is induced and catalyzed through graphene-loaded nickel, so that the graphitization temperature is reduced, the energy consumption is reduced, the graphitization crystalline structure is improved, and amorphous defects are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic devices, and in particular to a graphene thermal conductive film and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, the integration of electronic products is getting higher and higher, and the demand for microelectronic components has also increased significantly, which has also brought about problems such as high heat generation and uneven heat dissipation. Excessive heat seriously affects the normal operation of electronic devices and the stability of the system. Traditional thermal conductive materials are mainly metal materials such as copper foil and aluminum foil. Although these metal thermal conductive materials are relatively mature, they have disadvantages such as poor thermal conductivity, heavy weight, and poor corrosion resistance. It is difficult to meet the current electronic devices' demand for high thermal conductivity, light weight and high weather resistance of thermal conductive materials. Compared with traditional metal materials, graphene not only has higher thermal conductivity, but also shows advantages such as light weight and strong corrosion resistance. Based on this, graphene has greater potential in meeting the requirements of thermal conductive materials in the field of electronic devices. Among the various material forms of graphene, graphene can effectively meet the application scenarios of traditional metal thermal conductive materials such as aluminum foil and copper foil, so it has attracted much attention and has been deeply studied as a new generation of high-performance thermal conductive materials.

[0003] At present, there are four main methods for preparing graphene thermal conductive films, namely, expanded graphite calendering method, vapor deposition method, graphene oxide reduction method and polymer film graphitization method. Compared with the shortcomings of low thermal conductivity of expanded graphite calendering method, harsh conditions of vapor deposition method and serious pollution of graphene oxide reduction method, the graphene thermal conductive film prepared by polymer film graphitization method usually has good flexibility and thermal conductivity, and the process flow is simple. However, this method also has many defects, such as high energy consumption during high-temperature graphitization, and easy to produce a large amount of incompletely graphitized amorphous state, which seriously affects the thermal and electrical conductivity and production efficiency of the graphene thermal conductive film. Therefore, how to reduce the graphitization temperature, improve the graphitized crystalline structure, and reduce amorphous defects are important issues that need to be solved by the current graphene thermal conductive film. Summary of the invention

[0004] The technical problem to be solved by the present invention is that in the existing polymer film graphitization method, the temperature is high and the energy consumption is large, the graphitized crystalline structure is unstable, and there are amorphous defects.

[0005] The technical solution of the present invention to solve the above technical problem is: to provide a method for preparing a graphene thermal conductive film, comprising the following steps: a. Dispersing a water-soluble nickel salt in a solvent, and subjecting the solution to ultrasonic treatment to obtain a liquid A; dispersing graphene and a reducing agent in a solvent, adjusting the pH value to 11 to 13, and subjecting the solution to ultrasonic treatment to obtain a liquid B; b. Transfer liquid A and liquid B to a high-pressure reactor, add a surfactant, perform a hydrothermal reaction at 40-120° C. for 1-24 h, cool, centrifuge, wash, and then dry to obtain nickel-loaded graphene powder; c. Dissolve the nickel-loaded graphene powder and diamine in N,N-dimethylacetamide (DMAC), transfer to a high-pressure reactor, use nitrogen as a protective gas, add dianhydride to the reactor, react for 6 to 24 hours, and obtain a viscous polyamic acid solution; d. The viscous polyamic acid solution is uniformly coated on a 2×2 cm glass plate, and then imidized in a heating furnace at 100°C to 300°C for 1 to 6 hours to obtain a polyimide composite film, which is placed in an isostatically pressed graphite block and sent to a high-temperature graphitization furnace. In the high-temperature graphitization furnace, it is first carbonized at 800°C to 1200°C for 1 to 6 hours, and then graphitized at 1500°C to 3000°C for 1 to 6 hours to obtain a graphene thermal conductive film.

[0006] Wherein, in the preparation method of the above graphene thermal conductive film, the water-soluble nickel salt described in step a is at least one of nickel nitrate, nickel chloride, nickel bromide, nickel fluoride, nickel iodide, nickel sulfate, nickel hydroxide, nickel acetylacetonate or nickel acetate tetrahydrate, preferably nickel chloride.

[0007] Wherein, in the method for preparing the graphene thermal conductive film, the solvent in step a is at least one of water or ethanol, preferably water.

[0008] Wherein, in the above-mentioned method for preparing the graphene thermal conductive film, the concentration of the liquid A in step a is 0.01 to 0.5 mol / L, preferably 0.02 mol / L.

[0009] Wherein, in the method for preparing the graphene thermal conductive film, the reducing agent in step a is at least one of hydrazine hydrate, sodium borohydride, ascorbic acid or ethylene glycol, preferably hydrazine hydrate.

[0010] Among them, in the preparation method of the above-mentioned graphene thermal conductive film, the molar ratio of graphene: reducing agent in the B solution in step a is 0.5-16:1, preferably 5:1.

[0011] Among them, in the preparation method of the above-mentioned graphene thermal conductive film, the volume ratio of liquid A:liquid B in step a is 1:1-5.

[0012] Among them, in the preparation method of the above-mentioned graphene thermal conductive film, the pH is adjusted in step a using 1 mol / L sodium hydroxide solution.

[0013] Wherein, in the method for preparing the graphene thermal conductive film, the surfactant in step b is at least one of N-methylpyrrolidone, Triton or melamine, preferably N-methylpyrrolidone.

[0014] Wherein, in the above-mentioned method for preparing the graphene thermal conductive film, the amount of the surfactant added in step b is: the mass ratio of surfactant to graphene is 0.5 to 5:1, preferably 1:1.

[0015] Among them, in the above-mentioned method for preparing the graphene thermal conductive film, the reaction temperature in step b is preferably 70° C., and the reaction time is preferably 7 hours.

[0016] Wherein, in the preparation method of the above graphene thermal conductive film, the cooling in step b is natural cooling. The washing is washing with deionized water and ethanol for 3 times each. The drying is vacuum drying at a temperature of 50 to 100° C. for 2 to 24 hours, preferably vacuum drying at 60° C. for 12 hours.

[0017] In the above method for preparing the graphene thermal conductive film, the diamine in step c is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine, poly(p-phenylene terephthalamide) or 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, preferably 4,4'-diaminodiphenyl ether.

[0018] In the method for preparing the graphene thermal conductive film, the dianhydride in step c is at least one of pyromellitic dianhydride, 4,4'-biphenyl ether dianhydride, 1,2,4,5-benzene tetracarboxylic anhydride or 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, preferably pyromellitic dianhydride.

[0019] Wherein, in the preparation method of the above graphene thermal conductive film, the mass ratio of the nickel-loaded graphene powder to the diamine in step c is 1:1 to 10, preferably 1:4. The molar ratio of the diamine to the dianhydride is 1:1.

[0020] Among them, in the above-mentioned method for preparing the graphene thermal conductive film, the reaction time in step c is 8 hours.

[0021] In the above-mentioned method for preparing the graphene thermal conductive film, the imidization temperature in step d is 200°C for 1 hour, the carbonization temperature is 800°C for 1 hour, and the graphitization temperature is 1500°C for 1 hour.

[0022] The present invention also provides a graphene thermal conductive film directly prepared by the above method.

[0023] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a method for preparing a graphene thermal conductive film, wherein graphene-loaded nickel is used to induce and catalyze the graphitization of a polyimide film, thereby reducing the graphitization temperature. The graphitization temperature of a traditional method is 2500° C. to 3000° C., and the graphitization temperature of the invention can be reduced to 1500° C. at the lowest, thereby greatly reducing production energy consumption; improving the graphitized crystalline structure, and reducing amorphous defects. DETAILED DESCRIPTION

[0024] The invention mainly induces and catalyzes the graphitization of the polyimide film by loading nickel on graphene, thereby lowering the graphitization temperature and reducing the amorphous state.

[0025] Nickel is a catalyst that reduces the energy required for graphitization through catalytic action, allowing the graphitization process to be achieved at a relatively low temperature, improving production efficiency and reducing energy consumption.

[0026] The orbital hybridization of nickel atoms produces a small surface steric hindrance, which can effectively adsorb and stabilize carbon atoms, promoting them to form a more ordered graphite structure. As the reaction proceeds, amorphous carbon is gradually converted into graphite.

[0027] Therefore, the present invention reduces the graphitization temperature, reduces the energy consumption, and also reduces the defects of the amorphous state.

[0028] The specific implementation modes of the present invention will be further explained below through examples, but it is not intended to limit the protection scope of the present invention to the scope described in the examples. Example 1 Preparation of the nickel-catalyzed graphene thermal conductive film of the present invention,

[0029] The steps include: (1) Disperse 1 g of nickel chloride hexahydrate in 200 mL of aqueous solution and perform ultrasonic treatment to obtain solution A; (2) 8 g of graphene and 17 mL of hydrazine hydrate were dispersed in 800 mL of aqueous solution, the pH value was adjusted to 12 using 1 mol / L sodium hydroxide solution, and ultrasonic treatment was performed to obtain solution B; (3) Liquids A and B were transferred to a high-pressure reactor, and 8 g of N-methylpyrrolidone was added dropwise. The mixture was hydrothermally reacted at 70 °C for 7 h.

[0030] (4) After cooling naturally to room temperature, the sample was centrifuged, washed three times with deionized water and three times with ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain graphene-loaded nickel nanoparticle powder.

[0031] (5) Graphene-loaded nickel nanoparticle powder and 0.2 mol 4,4'-diaminodiphenyl ether were dissolved in 1 L DMAC and transferred into a high-pressure reactor using nitrogen as the protective gas.

[0032] (6) Add 0.2 mol of isophthalic acid dianhydride into the reaction kettle and react for 8 h to obtain a viscous polyamic acid solution.

[0033] (7) The polyamic acid solution was uniformly coated on a 2×2 cm glass plate and then imidized in a heating furnace at 200 °C for 1 h to obtain a PI composite film.

[0034] (8) Place the PI film into an isostatically pressed graphite block and send it into a high-temperature graphitization furnace.

[0035] (9) In a high-temperature graphitization furnace, the graphite is first carbonized at 800°C for 1 h and then graphitized at 1500°C for 1 h to obtain a graphene thermal conductive film. Example 2 Preparation of the nickel-catalyzed graphene thermally conductive film of the present invention,

[0036] The steps include: (1) Disperse 4 g of nickel chloride hexahydrate in 200 mL of aqueous solution and perform ultrasonic treatment to obtain solution A; (2) 8 g of graphene and 0.8 mL of hydrazine hydrate were dispersed in 800 mL of aqueous solution, the pH value was adjusted to 11 using 1 mol / L sodium hydroxide solution, and ultrasonic treatment was performed to obtain solution B; (3) Liquid A and Liquid B were transferred to a high-pressure reactor, and 8 g of N-methylpyrrolidone was added dropwise. The mixture was hydrothermally reacted at 90 °C for 12 h.

[0037] (4) After cooling naturally to room temperature, the sample was centrifuged, washed three times with deionized water and three times with ethanol, and dried in a vacuum drying oven at 80 °C for 6 h to obtain graphene-loaded nickel nanoparticle powder.

[0038] (5) Graphene-loaded nickel nanoparticle powder and 0.2 mol 4,4'-diaminodiphenyl ether were dissolved in 1 L DMAC and transferred into a high-pressure reactor using nitrogen as the protective gas.

[0039] (6) Add 0.2 mol of isophthalic acid dianhydride into the reaction kettle and react for 16 h to obtain a viscous polyamic acid solution.

[0040] (7) The polyamic acid solution was uniformly coated on a 2×2 cm glass plate and then imidized in a heating furnace at 150 °C for 2 h to obtain a PI composite film.

[0041] (8) Place the PI film into an isostatically pressed graphite block and send it into a high-temperature graphitization furnace.

[0042] (9) In a high-temperature graphitization furnace, the film is first carbonized at 1000°C for 2 h and then graphitized at 2400°C for 2 h to obtain a graphene thermal conductive film. Example 3 Preparation of the nickel-catalyzed graphene thermal conductive film of the present invention,

[0043] The steps include: (1) Disperse 0.5 g of nickel chloride hexahydrate in 200 mL of aqueous solution and perform ultrasonic treatment to obtain solution A; (2) 8 g of graphene and 0.8 mL of hydrazine hydrate were dispersed in 800 mL of aqueous solution, the pH value was adjusted to 13 using 1 mol / L sodium hydroxide solution, and ultrasonic treatment was performed to obtain solution B; (3) Liquids A and B were transferred to a high-pressure reactor, and 8 g of N-methylpyrrolidone was added dropwise. The mixture was hydrothermally reacted at 50 °C for 24 h.

[0044] (4) After cooling naturally to room temperature, the sample was centrifuged, washed three times with deionized water and three times with ethanol, and dried in a vacuum drying oven at 70°C for 24 h to obtain graphene-loaded nickel nanoparticle powder.

[0045] (5) Graphene-loaded nickel nanoparticle powder and 0.2 mol 4,4'-diaminodiphenyl ether were dissolved in 1 L DMAC and transferred into a high-pressure reactor using nitrogen as the protective gas.

[0046] (6) Add 0.2 mol of isophthalic acid dianhydride into the reaction kettle and react for 12 h to obtain a viscous polyamic acid solution.

[0047] (7) The polyamic acid solution was uniformly coated on a 2×2 cm glass plate and then imidized in a heating furnace at 300 °C for 5 h to obtain a PI composite film.

[0048] (8) Place the PI film into an isostatically pressed graphite block and send it into a high-temperature graphitization furnace.

[0049] (9) In a high-temperature graphitization furnace, the graphene is first carbonized at 900°C for 1 h and then graphitized at 2000°C for 1 h to obtain a graphene thermal conductive film. Example 4 Preparation of the nickel-catalyzed graphene thermally conductive film of the present invention,

[0050] The steps include: (1) Disperse 1 g of nickel chloride hexahydrate in 200 mL of aqueous solution and perform ultrasonic treatment to obtain solution A; (2) 8 g of graphene and 1.3 g of sodium borohydride were dispersed in 800 mL of aqueous solution, the pH value was adjusted to 12 using 1 mol / L sodium hydroxide solution, and ultrasonic treatment was performed to obtain solution B; (3) Liquids A and B were transferred to a high-pressure reactor, and 8 g of N-methylpyrrolidone was added dropwise. The mixture was hydrothermally reacted at 70 °C for 8 h.

[0051] (4) After cooling naturally to room temperature, the sample was centrifuged, washed three times with deionized water and three times with ethanol, and dried in a vacuum drying oven at 70 °C for 12 h to obtain graphene-loaded nickel nanoparticle powder.

[0052] (5) Graphene-loaded nickel nanoparticle powder and 0.2 mol 4,4'-diaminodiphenyl ether were dissolved in 1 L DMAC and transferred into a high-pressure reactor using nitrogen as the protective gas.

[0053] (6) Add 0.2 mol of isophthalic acid dianhydride into the reaction kettle and react for 12 h to obtain a viscous polyamic acid solution.

[0054] (7) The polyamic acid solution was uniformly coated on a 2×2 cm glass plate and then imidized in a heating furnace at 200 °C for 1 h to obtain a PI composite film.

[0055] (8) Place the PI film into an isostatically pressed graphite block and send it into a high-temperature graphitization furnace.

[0056] (9) In a high-temperature graphitization furnace, the product is first carbonized at 1100°C for 1 h and then graphitized at 2600°C for 1 h to obtain a graphene thermal conductive film. Example 5 Preparation of the nickel-catalyzed graphene thermal conductive film of the present invention,

[0057] The steps include: (1) Graphene powder and 0.2 mol 4,4'-diaminodiphenyl ether were dissolved in 1 L DMAC and transferred into a high-pressure reactor using nitrogen as the protective gas.

[0058] (2) Add 0.2 mol of isophthalic acid dianhydride into the reaction kettle and react for 8 h to obtain a viscous polyamic acid solution.

[0059] (3) The polyamic acid solution was uniformly coated on a 2×2 cm glass plate and then imidized in a heating furnace at 200 °C for 1 h to obtain a PI composite film.

[0060] (4) Place the PI film into an isostatically pressed graphite block and send it into a high-temperature graphitization furnace.

[0061] (5) In a high-temperature graphitization furnace, the product is first carbonized at 1200°C for 1 hour and then graphitized at 3000°C for 1 hour to obtain a graphene thermal conductive film.

[0062] It can be seen from the embodiments that the present invention can load nickel nanoparticles on graphene to uniformly disperse graphene and nickel in the PI film, thereby effectively inducing and catalyzing the graphitization of polyimide during graphitization, reducing the graphitization temperature, and improving the graphitized crystalline structure, so as to achieve the production of graphene thermal conductive film with lower energy consumption and better structure.

[0063] The graphitization temperature and thermal conductivity of the graphene thermal conductive films prepared in various embodiments are shown in Table 1 below: Example 1 Example 2 Example 3 Example 4 Example 5 Graphitization temperature℃ 1500 2400 2000 2600 3000 <![CDATA[Thermal conductivity W / (m -1 ·K -1 )]]> 2375 2079 2146 2052 1823 After multiple experimental adjustments, the number of nickel nanoparticles in Example 1 is relatively large, the particle size is 40-60 nm, and the nickel nanoparticles are evenly distributed among the graphene. Therefore, the catalytic effect on graphitization is the most significant, the graphitization temperature is low, and the graphene thermal conductive film finally formed has a good crystalline structure and fewer amorphous defects, thereby having excellent thermal conductivity. In Example 2, due to insufficient reducing agent and low pH value, the degree of reduction is low, the number of nickel nanoparticles is small, and the particle size is uneven, so the catalytic effect is not obvious, and the reduction of graphitization temperature is small. At the same time, the nickel nanoparticles are unevenly distributed among the graphite, resulting in that although the crystalline structure of the graphene thermal conductive film is improved, there are still many amorphous defects, which makes the thermal conductivity performance limited; In Example 3, the reducing agent is sufficient, but the reaction time is too long, resulting in the continued growth of nickel nanoparticles after they are generated, resulting in agglomeration, and the emergence of many large-sized nickel nanoparticles. Although the graphitization is catalytic, the size and distribution of the nickel nanoparticles are uneven, and the crystalline structure of the graphene thermal conductive film produced in the end still has certain amorphous defects; In Example 4, the nickel nanoparticles obtained by sodium borohydride reduction have poor dispersibility and are easily agglomerated to form nickel nanoparticles with large particle sizes. Boron impurities are also introduced, which hinder the catalytic effect of nickel. Therefore, the catalytic effect on graphitization is not as good as that of nickel nanoparticles reduced by hydrazine hydrate. Example 5 is a graphene thermally conductive film without adding nickel nanoparticles. With the addition of graphene, the thermal conductivity of the graphite thermally conductive film is improved, but the graphitization temperature requirement is still high and the energy consumption is large.

Claims

1. A method for preparing a graphene thermally conductive film, characterized in that: The following steps are involved: a. Dispersing a water-soluble nickel salt in a solvent, and subjecting the solution to ultrasonic treatment to obtain a liquid A; dispersing graphene and a reducing agent in a solvent, adjusting the pH value to 11 to 13, and subjecting the solution to ultrasonic treatment to obtain a liquid B; b. Transfer liquid A and liquid B to a high-pressure reactor, add a surfactant, perform a hydrothermal reaction at 40-120° C. for 1-24 h, cool, centrifuge, wash, and then dry to obtain nickel-loaded graphene powder; c. Dissolve the nickel-loaded graphene powder and diamine in N,N-dimethylacetamide (DMAC), transfer to a high-pressure reactor, use nitrogen as a protective gas, add dianhydride to the reactor, react for 6 to 24 hours, and obtain a viscous polyamic acid solution; d. The viscous polyamic acid solution is uniformly coated on a 2×2 cm glass plate, and then imidized in a heating furnace at 100°C to 300°C for 1 to 6 hours to obtain a polyimide composite film, which is placed in an isostatically pressed graphite block and sent to a high-temperature graphitization furnace. In the high-temperature graphitization furnace, it is first carbonized at 800°C to 1200°C for 1 to 6 hours, and then graphitized at 1500°C to 3000°C for 1 to 6 hours to obtain a graphene thermal conductive film.

2. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: The water-soluble nickel salt described in step a is at least one of nickel nitrate, nickel chloride, nickel bromide, nickel fluoride, nickel iodide, nickel sulfate, nickel hydroxide, nickel acetylacetonate or nickel acetate tetrahydrate.

3. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: The concentration of the liquid A in step a is 0.01-0.5 mol / L; the molar ratio of graphene to reducing agent in the liquid B is 0.5-16:1; and the volume ratio of the liquid A to the liquid B is 1:1-5.

4. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: The surfactant in step b is at least one of N-methylpyrrolidone, Triton or melamine.

5. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: The amount of surfactant added in step b is such that the mass ratio of surfactant to graphene is 0.5 to 5:

1.

6. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: The diamine in step c is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine, poly(p-phenylene terephthalamide) or 4,4'-(hexafluoroisopropylidene)diphthalic anhydride.

7. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: In step c, the dianhydride is at least one of pyromellitic dianhydride, 4,4'-biphenyl ether dianhydride, 1,2,4,5-benzenetetracarboxylic anhydride or 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene.

8. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: In step c, the mass ratio of the nickel-loaded graphene powder to the diamine is 1:1-10; and the molar ratio of the diamine to the dianhydride is 1:

1.

9. The method for preparing the graphene thermally conductive film according to claim 1, characterized in that: In step d, the imidization temperature is 200°C and the time is 1 hour; the carbonization temperature is 800°C and the carbonization time is 1 hour; and the graphitization temperature is 1500°C and the time is 1 hour.

10. The graphene thermally conductive film prepared by the method for preparing the graphene thermally conductive film according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for manufacturing substrates of three-dimensional graphene-nickel oxide composite materials

    CN103681003A

  • Preparation method of graphene-polyimide composite heat conducting film

    CN106045515A

  • Method for preparing high thermal conductivity graphite film by using graphene-doped polyamic acid resin

    CN106853966A

  • Graphene-loaded nickel magnetic composite material preparation method

    CN109107528A

  • Graphene induced polyimide oriented crystallization based high-thermal-conductivity graphite film preparation method

    CN110304625A